Pengaruh Perawatan Pencegahan frekwensi gerinda Top Roller terhadap ketidakrataan sliver kapas 100 % Drawing Breaker pada pabrik pemintalan benang - Giyanto, Giyanto (Jurnal Ilmiah Fakultas Teknik, 2025)
Good and bad sliver breaker draw frame will cause good or bad yarn unevenness that will be produced, because breaker draw frame sliver is a series of sequences of cotton yarn manufacturing process. Yarn with a high unevenness value indicates that the yarn has many thick and thin spots in the cross section of the yarn. Yarn with a high unevenness value will cause the yarn to break in thin places, thus affecting production efficiency. For this reason, research was carried out on the breaker draw frame on process parameters that could cause high unevenness values.?The study was conducted in a Drawing breaker machine using a completely randomized design (CRD) with three replications. The factors studied were the top roller grinding frequency which consisted of a frequency of 4 weeks, 5 weeks, 6 weeks, 7 weeks and 8 weeks. Analysis of the data used to analyze the analysis of variance (Anova) one way. Because the expected sliver unevenness is as low as possible, the criterion used is that the smaller the better. The experimental results show that the top roller grinding frequency every 4 weeks produces the lowest sliver unevenness value (? %) which is 2.47.